2021
DOI: 10.1017/jwe.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

Merging One's Way to the Top: AB Inbev versus Heineken

Abstract: Leuven's Den Hoorn brewery, now AB Inbev SA, has become the world's largest brewing group by far, but critics say the company overpaid for its acquisitions. In this article, we study typical stock market reactions to the many takeover announcements by AB Inbev and the industry's runner-up, Heineken. Unlike Heineken's, the market leader's takeover announcements were met by, on average, a –2% price reaction in the stock market in the announcement month, but most of that is already undone in the next month. For H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Our methodological contribution is a parsimonious hybrid of distributed lags and a spline that allows us to identify multiperiod post-event reaction patterns on the basis of two parameters, a shape parameter that identifies the post-event return pattern as either monotonic or whip-shaped, and a scaler that determines the sign and size of the reaction. In our application, we introduce this into the mean equation that comes with an augmented-GARCH variance equation, and we study the drop-and-recovery price pattern observed after takeover announcements by AB Inbev SA and Heineken (Doan and Sercu, 2020). The main competing hypotheses are a slowly resolved uncertainty about the deal's merits versus an indiscriminate but temporary distrust about the management's motives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our methodological contribution is a parsimonious hybrid of distributed lags and a spline that allows us to identify multiperiod post-event reaction patterns on the basis of two parameters, a shape parameter that identifies the post-event return pattern as either monotonic or whip-shaped, and a scaler that determines the sign and size of the reaction. In our application, we introduce this into the mean equation that comes with an augmented-GARCH variance equation, and we study the drop-and-recovery price pattern observed after takeover announcements by AB Inbev SA and Heineken (Doan and Sercu, 2020). The main competing hypotheses are a slowly resolved uncertainty about the deal's merits versus an indiscriminate but temporary distrust about the management's motives.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest in within-window CAR patterns over such an intermediate horizon was actuated by Doan and Sercu (2020)'s study of takeovers by the brewing industry's two leading firms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beer industry has been the focus of countless market structure and pricing studies, for example, Hellerstein (2008) and Goldberg and Hellerstein (2013) on exchange rate pass-through; Alviarez, Head, and Mayer (2021) and Doan and Sercu (2021) on multinational mergers and acquisitions ;Miller, Sheu, and Weinberg (2021) on oligopolistic price leadership and mergers; and Anderson (2023), Elzinga (2011), Elzinga, Tremblay, andTremblay (2015), andMcCullough, Berning, andHanson (2019) on changing market structures. But until now, access to granular level of data on production and distribution of small breweries has either been proprietary, such as on-premise sales data collected by brewers, or comes at a hefty cost, such as primary collected data (e.g., Hart, 2018;Staples et al, 2020) or scanner-level data collected by companies like Nielsen and IRI (see Volpe et al, 2016;Rojas and Peterson, 2008;Burgdorf, 2019).…”
Section: Introductionmentioning
confidence: 99%